Cyclophilin inhibitors for HCV - Flisiak, Robert (Henry Stewart Talks, 2011)
HCV infection and its consequences, Role of cyclophilins in HCV replication, Anti-HCV effect of cyclophilin inhibitors, Development of non-immunosuppressive cyclophilin inhibitors, Clinical studies on possible use of cyclophilin inhibitors for hepatitis C treatment, Efficacy and low risk of resistance